2001
DOI: 10.1136/fn.84.1.f40
|View full text |Cite
|
Sign up to set email alerts
|

Study of maternal influences on fetal iron status at term using cord blood transferrin receptors

Abstract: Conclusions-Maternal iron depletion is associated with reduced fetal iron stores but no change in free iron availability. Smoking is associated with increased fetal iron requirements for erythropoiesis. (Arch Dis Child Fetal Neonatal Ed 2001;84:F40-F43)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 26 publications
8
45
0
2
Order By: Relevance
“…Higher levels of ferritin in cord blood can be attributed to active transport of iron to the fetus. Nevertheless, several studies have shown that in severe maternal anaemia these active pathways may fail [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of ferritin in cord blood can be attributed to active transport of iron to the fetus. Nevertheless, several studies have shown that in severe maternal anaemia these active pathways may fail [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan bazı çalışmalarda, gebelerdeki demir eksikliğinin, fetus ve infarıtın demir durumunu etkilediği, prematür doğum prevalansını artırdığı, uzun dönemde büyüme ve gelişme geriliğine neden olabileceği gösteril-miştir (5)(6)(7)(8). Bazı çalışmalarda da annenin demir durumunun bebeğin demir durumuna etkisi olmadığı, bebeklerin demir depolannın ilk dört ay için yeterli olduğu bildirilmiştir (9-1 1).…”
Section: Ssk Tepecik Hast Derg 2004;14(3)g153-162unclassified
“…[6,7] Sweet et al reported that sTfR measurement could replace other assays for iron deficiency state especially in subclinical iron deficiency present in their study population which was undetected by these other assays. [8] There is no difference between sTfR concentrations in healthy males and females, [9,10] but the values are higher in children compared to adults. [11] However, Blacks have a higher sTfR concentration than non-blacks.…”
Section: Introductionmentioning
confidence: 99%
“…[11] However, Blacks have a higher sTfR concentration than non-blacks. [12] This difference may be related to the well-known but unexplained difference in haemoglobin concentrations in Blacks and Caucasians.Therefore, misdiagnosis of Some studies have also shown that sTfR is increased in blood donors, [13] during physical exercise, [14,15] cigarette smoking, [8] and high altitude, [16] where reduced oxygen tension necessitates increased erythropoiesisbut is reduced by ascorbic acid administration and iron supplementation. [17,18] A blood donor loses about 200-250 mg of iron with every unit of 450mls of blood donated.…”
Section: Introductionmentioning
confidence: 99%